Panmaskarada. Maski i maskowanie u Brunona Schulza - Tomczok, Paweł (Er(r)go. Teoria - Literatura - Kultura, 2018)
For and abstract in Polish, scroll down Paweł Tomczok Institute of Polish Literature Faculty of Philology University of Silesia in Katowice Poland Panmasquerade. Masks and Masking in Bruno Schulz’s Fiction Abstract: The author of this article analyses different meanings of mask in Bruno Schulz’s fiction and non-fiction. In his critical statements Schulz contrasts mask with substance, the latter capable of assuming various masks. Taking into account the context of Cinnamon Shops, this can be read as a commentary on Schulz’s writing practice and as a strategy thus to mask his own biography. Another theme discussed in this article is that of the relation between mask and face in Schulz’s short stories. This discussion focuses on the social context of the different representations of the face and on the elimination of dialogues from the narratives: the narrator treats the characters’ facial features as source of knowledge about the world, rather than conversations with them. Keywords: Bruno Schulz, mask, autobiography For abstract in English, scroll down. Panmaskarada. Maski i maskowanie u Brunona Schulza Abstrakt: Celem artykułu jest omówienie różnych znaczeń maski w prozie i eseistyce Brunona Schulza. W wypowiedziach krytycznych pisarz wprowadza opozycję między maską a substancją – substancja przyjmuje różne maski. Te wypowiedzi odnoszą się także do praktyki pisarskiej autora Sklepów cynamonowych, który dokonuje zamaskowania własnej biografii. W artykule omawiam także relację między maską a twarzą w opowiadaniach Schulza – a szczególnie kontekst społeczny różnych przedstawień twarzy oraz zagadnienia eliminacji dialogu z opowiadań. Narrator nie czerpie informacji o świecie z rozmów z bohaterami, lecz raczej opisuje ich fizjonomię. Słowa kluczowe: Bruno Schulz, Bruno Schulz, maska, autobiografia